Formation Mechanism of Lotus-root-shaped Nanostructure during Two-step Anodization. (10th January 2016) - Jin, Rong; Fan, Haowen; Liu, Yuting; Ma, Wan; Lu, Hongyan; Yang, Peng; Ma, Weihua
Highlights: Under the same voltage, lotus-root-shaped nanostructure is found for the first time. New explanation for the lotus-root-shaped nanostructure is presented. The concave or patterned substrate fails to guide pore growth in second anodization. The anion contaminated layer (ACL) is formed near the residual concaves. Lotus-root-shaped nanostructure disappears with the disappearance of hexagonal ACL. Abstract: Anodic TiO2 nanotubes (ATNTs) have been widely investigated due to their interesting formation mechanism. The general accepted mechanism is the field-assisted dissolution theory. Here, two-step anodization processes under different voltages and various lotus-root-shaped nanostructures have been studied in detail. When the applied voltage of second anodization is the same as that of first anodization, lotus-root-shaped nanostructure is found for the first time. These lotus-root-shaped nanostructures of ATNTs can not be elucidated by the field-assisted dissolution. Based on the oxygen bubble mould and the oxide flow model, new explanation for the lotus-root-shaped nanostructure is presented. The anion contaminated layer (ACL) formed around the residual concaves plays critical roles in the formation of lotus-root-shaped nanostructure. When the hexagonal stripes and the mesh-like coverage of anion contaminated layer covered on the nanotubes disappear, the lotus-root-shaped nanostructures will vanish away.